Descrição da sintomatologia e análise da proteína kin17 em lagartas de Bombyx mori submetidas à intoxicação pelo inseticida chlorantraniliprole - Pessini, Graziele Milani (2014)
Chlorantraniliprole is the main compound of a new insecticide and its aerial spraying near mulberry plantations has been caused several damages to the silkworm (Bombyx mori) producers. In this work, the effects of chlorantraniliprole insecticide were analyzed in different instars of B. mori larvae. Different doses of the insecticide were administrated by immersion of the mulberry leaves and then offered to the larvae. Were observed that, in high concentration of chlorantraniliprole (0,2 ppm and 0,1 ppm), the mortality rate of larvae were 100%. Besides, symptoms such as feeding cessation, regurgitation, late development and incomplete ecdysis were frequent. Other common symptoms in sub-lethal concentrations (0,025, 0,0125, 6,25 x 10-3, 3,13 x 10-3 e 1,57 x 10-3 ppm) were rosary-shaped excrements and production of thin-shelled cocoons. The histological analysis revealed that chlorantraniliprole cause serious morphological changes in the internal midgut, both to the epithelial coating and its associate muscles, modifying its physiological functions and the insect survival. The results obtained in immunodetection, using the antibody against kin17 protein in larval tissue of B. mori, showed that there was no expression of this protein, both in larval tissue of the control group and the larvae intoxicated with 0,025 ppm of the insecticide, this results suggests that, in B. mori, kin17 protein is not associated with process of cellular stress by intoxication using this class of insecticide tested. Thus, we can conclude that chlorantraniliprole, in high concentrations, caused significant mortality rates, affect the larvae development in B. mori and in the sub-letal concentrations, the amount of regular cocoons were reduced.